2003 Handbook of Employment Regulations Affecting Florida Farm Employers and Workers: Transportation of Migrant Farm Workers [State] - Leo C. Polopolus; Michael T. Olexa; Fritz Roka; Carol Fountain (EDIS)
The purpose of having Transportation of Migrant Farm Workers regulations is to provide state standards for transporters of migrant farmworkers. This is EDIS document FE419, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Published July 2003. This information is included in Circular 1200, Handbook of Employment Regulations Affecting Florida Farm Employers and Workers.